KORELASI KEHADIRAN DENGAN HASIL BELAJAR MAHASISWA TEKNIK MESIN UNIVERSITAS MUHAMMADIYAH TANGERANG DI ERA NEW NORMAL - Rofiroh Rofiroh; Isnaini Mahuda; Nurhayati Nurhayati (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2022)
Correlation can be said to be a fact of the relationship between two or more variables. This study aims to determine the correlation between attendance and learning outcomes of Mechanical Engineering Students at Muhammadiyah University of Tangerang in the new normal era. The research method used is a quantitative method with a correlation of two variables. Analysis of attendance variables with student learning outcomes using the product moment calculation method. The results showed that the correlation between attendance and student learning outcomes had a very small and not close effect, namely 0.38. This shows that 14.8% of learning outcomes are influenced by attendance and 85.2% are influenced by other factors